Ibu ANALISIS RANTAI PASOK DAN NILAI TAMBAH AGROINDUSTRI KOPI DI KECAMATAN CIKAJANG KABUPATEN GARUT: MENYUSURI PELUANG PASAR DAN DAYA SAING LOKAL - Rawati, Fitrin; Purnamasari, Imas; Oktaroza, Magnaz. L. (Fakultas Ekonomi Universitas Garut, 2025)
Coffee plays a vital role in Indonesia’s rural economy, contributing not only to employment and foreign exchange earnings but also to regional development through agro-industrial linkages. However, local coffee-producing regions such as Cikajang in Garut Regency still face structural inefficiencies in their supply chains, resulting in unequal value distribution and weak competitiveness compared to other producing areas. Understanding the mechanisms of value creation and efficiency within this supply chain is therefore essential to enhance farmers’ welfare and regional competitiveness.This study aims to: (1) identify the structure of the Arabica coffee supply chain in Cikajang District, along with the roles and activities of actors at each stage; (2) measure value added at different processing levels using the Hayami method; (3) analyze the marketing efficiency of Cikajang Arabica coffee through the calculation of cost–product value ratios; and (4) examine the potential for strengthening competitiveness by improving supply chain efficiency. The results indicate that farmers remain positioned upstream with limited involvement in downstream processes, while value added increases significantly at the roasting stage, which yields the highest profit margins. The marketing efficiency analysis reveals that shorter distribution channels—such as farmer–farmer group association–roastery–consumer—are more efficient (EP 5.85%) compared to longer channels involving multiple actors. The structure of value added and marketing efficiency underscores an imbalance in profit distribution across the supply chain. Strengthening competitiveness can be achieved through farmer capacity building, cooperative institution development, distribution and logistics efficiency, geographical identity–based branding, and product diversification. These findings provide strategic implications for developing a more efficient, equitable, and sustainable local coffee supply chain.